2012
DOI: 10.1007/s12010-012-0014-0
|View full text |Cite
|
Sign up to set email alerts
|

In Silico and Experimental Characterization of Chimeric Bacillus thermocatenulatus Lipase with the Complete Conserved Pentapeptide of Candida rugosa Lipase

Abstract: Lipases are one of the highest value commercial enzymes as they have broad applications in detergent, food, pharmaceutical, and dairy industries. To provide chimeric Bacillus thermocatenulatus lipase (BTL2), the completely conserved pentapeptide (¹¹²Ala-His-Ser-Gln-Gly¹¹⁶) was replaced with similar sequences (²⁰⁷Gly-Glu-Ser-Ala-Gly²¹¹) of Candida rugosa lipase (CLR) at the nucleophilic elbow region. For this purpose, three mutations including A112G, H113E, and Q115A were inserted in the conserved pentapeptide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…The pKHT.E plasmid containing chimeric btl2 gene (previous work) was used as a template for generating mutated btl2 gene using site-directed mutagenesis, as described previously [16]. The mutated btl2 gene was generated by PCR using the F17S forward (5′- GA TGGCCA TGGCGGCATCCCCACGCGCCAATGATGCACCCATCGTGCTTCTCCATGGG TCC ACAGGATGGGGGCGAGAG-3′, Mlu NI site and point mutation are underlined) and F17S reverse (5′- TT GAGCTC ATCATC CCTTCATTAAGGC -3′, Sac I site) primers.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The pKHT.E plasmid containing chimeric btl2 gene (previous work) was used as a template for generating mutated btl2 gene using site-directed mutagenesis, as described previously [16]. The mutated btl2 gene was generated by PCR using the F17S forward (5′- GA TGGCCA TGGCGGCATCCCCACGCGCCAATGATGCACCCATCGTGCTTCTCCATGGG TCC ACAGGATGGGGGCGAGAG-3′, Mlu NI site and point mutation are underlined) and F17S reverse (5′- TT GAGCTC ATCATC CCTTCATTAAGGC -3′, Sac I site) primers.…”
Section: Methodsmentioning
confidence: 99%
“…Lipase activity was determined by triacylglycerol substrates in pH-STAT (Metrohm Ltd., Herisau, Switzerland) at 55 °C (pH 9.5). For substrate specificity, 2 mg/ml of various substrate, including tributyrin (C4), tricaprylin (C8), tricaprin (C10), trilaurin (C12), trimyristin (C14), tripalmitin (C16), and olive oil (C18) were emulsified in distilled water containing Arabic gum (20 mg/ml) using ultrasonic treatment (Hielscher GmbH, Teltow, Germany) for 5 min at maximum power [16].…”
Section: Methodsmentioning
confidence: 99%
“…Thermal inactivation is critical for both reusability and storage stability. One possible approach for improvement is to use thermally stable lipases [39,40]. Because large amount of lipase-bound MNP was used for the transesterification, those away from the magnetic field were easily washed off during recycling.…”
Section: Discussionmentioning
confidence: 99%
“…The pentapeptide is essential for lipase activity; however, little is known about its role in catalytic performance [ 11 ]. In order to explore its function, Hosseini et al (2013) [ 12 ] replaced the pentapeptide AHSMG in the lipase BTL2 of Bacillus thermocatenulatus with the pentapeptide GGSAG, found in CRL lipase of Candida rugosa . It was observed that the native AHSMG-lipase retained 50% of its activity after 60 min at 65 °C, 80% at pH 9, and about 75% at pH 10.…”
Section: Introductionmentioning
confidence: 99%